In Vitro Antioxidant and Cytotoxic Activities of Some Marine Sponges Collected off Misamis Oriental Coast, Philippines - A. P. Rivera; M. M. Uy (E-Journal of Chemistry)
The phosphomolybdenum method for total antioxidant activity determination showed that the hexane, dichloromethane and ethyl acetate extracts of five marine sponge species collected off misamis oriental coast-Aaptos suberitoides, Dactylospongia elegans, Stylissa massa, Haliclona sp. and an unidentified species coded as KL-05, have varying degrees of antioxidant capacity. Expressed as ascorbic acid equivalents in μg/mL of extract, the hexane extract of Dactylospongia elegans (DeH) and the ethyl acetate extract of Aaptos suberitoides (AsE) showed the highest antioxidant capacity. Although the hexane extract of KL-05 (KL-05H) has considerable antioxidant activity, the ethyl acetate extract (KL-05E) showed no antioxidant activity. The brine shrimp assay for cytotoxicity indicated high bioactivity, with Haliclona sp., Dactylospongia elegans, Aaptos suberitoides and Stylissa massa exhibiting high % mortality and low LC50 values. The antioxidant and cytotoxic activities of the marine sponges may be attributed to the zoochemicals present. All sponge species contain alkaloids, saponins, tannins, and flavonoids. Terpenoids are present only in Haliclona sp. and the cardiac glycosides, only in Aaptos suberitoides and Haliclona sp.